Understanding the out-of-class English Learning Choices of Students in Taiwan - Charles Allen Brown (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2017)
Research has established that successful foreign language students often seek out opportunities to supplement their language studies with out-of-class language practice. Little is known, however, about the forms of out-of-class English studies in which successful English learners in Taiwan engage with the reasons for these particular choices being especially unclear. To address this gap, this project considered the out-of-class English learning choices of 79 university English majors in Taiwan. Findings based upon ethnographic interviews with these individuals indicate that they believed out-of-class English practice to be important due to the limitations associated with their formal language study. Despite this impetus, their choices of settings and interlocutors for English practice were constrained by beliefs about language circulating in the society, in particular social censure associated with English use in public places and with other Taiwanese. As a result, they tended to practice English in online venues, within the confines of the home, with like-minded peers, and with those perceived as foreigners. These results extend our understanding of out-of-class English study by addressing it as a socially-situated phenomenon, foregrounding the sorts of constraints that even highly-motivated language learners may face in their efforts to build their language proficiency.